2017
DOI: 10.5539/gjhs.v9n9p81
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance among Teaching Hospital Nurses in Malaysia

Abstract: Extreme workload and poor working environment have a negative impact on the emotional and physical statuses among nurses. The study has contributed to evaluate work-life balance and its related factors among teaching hospital nurses. It was aimed to examine the work-life balance and its related factors among teaching hospital nurses. A cross-sectional study using a universal sampling technique was conducted. 1002 nurses were included from the Teaching hospital of Klang Valley, Malaysia. The instrument was adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…This finding supports Dousin et al., (2019) and Nurumal et al. (2017) who argue that WLB balance practices have benefits for both employees and employers. At a time of nurse shortages in Malaysian hospitals, WLB practices can contribute to nurse retention.…”
Section: Discussionsupporting
confidence: 86%
“…This finding supports Dousin et al., (2019) and Nurumal et al. (2017) who argue that WLB balance practices have benefits for both employees and employers. At a time of nurse shortages in Malaysian hospitals, WLB practices can contribute to nurse retention.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, those nurses working shifts (n=384), were having satisfactory QoWL (Table 3). This finding was found to be contradicted with the study by Nurumal, Makabe, Ilyani et al, (2017) that showed nurses who are working in fixed shifts, such as office hours, were observed with more outstanding work-life balance as compared to the nurses working in rotational shifts or multiple shifts. Nurses were required to work more than 12 hours per day for few days during the pandemic.…”
Section: 8contrasting
confidence: 56%
“…( 2019 ) and Nurumal et al. ( 2017 ), which stated that flexible working hours will improve nurses’ job satisfaction which is a critical factor to nurse retention. This work practice is a part of organizational work‐life balance practices, which is important to reduce employees’ emotional labour and burnout, which could reduce their intention to leave (Bartram et al., 2012 ; Cheng et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%